2021
DOI: 10.1088/1755-1315/653/1/012124
|View full text |Cite
|
Sign up to set email alerts
|

The characteristic of different formula of low tannin sorghum instant porridge

Abstract: Sorghum has a potential to be developed as staple food, however the main obstacle is high tannin content which causing bitter taste. Low conttent of tannin in sorghum flour could be a solution for widening the customer acceptance. Such product produced using low tannin sorghum is instant porridge. Therefore this study aimed to find optimum formula of instant porridge using low tannin sorghum flour. This study using two factors of instant porridge formula, first ratio of low tannin sorghum flour : tapioca (100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The following step is grinding the flakes into instant sorghum flour, adding 30 and 40% full cream milk and sugar, respectively. This instant sorghum porridge is ready to be consumed after being poured with hot water [24,29]. Instant sorghum porridge with this formula contains 10.1% protein (db), 2.46% fat (db), and energy 388.9 Kcal/100g.…”
Section: Innovation Products Of Sorghum Flourmentioning
confidence: 99%
“…The following step is grinding the flakes into instant sorghum flour, adding 30 and 40% full cream milk and sugar, respectively. This instant sorghum porridge is ready to be consumed after being poured with hot water [24,29]. Instant sorghum porridge with this formula contains 10.1% protein (db), 2.46% fat (db), and energy 388.9 Kcal/100g.…”
Section: Innovation Products Of Sorghum Flourmentioning
confidence: 99%
“…Ancient grains are more tolerant to biotic and abiotic stresses [8] and often contain more protein, dietary fibre, bioactive compounds and antioxidant activity and show improved health benefits (see Tables 1 and 2). Anti-cancer Improving gut health [41,44] Comparing ancient wheat and modern wheat for their potential to elicit coeliac disease has found similar immunoreactivity of both cultivars and, hence, the breeding of modern wheat is not responsible for the prevalence of coeliac disease [45,46]. Preliminary in vivo and in vitro studies indicated that the consumption of different ancient grains could be better tolerated by non-coeliac wheat-sensitive individuals and those who suffer from irritable bowel syndrome.…”
Section: Ancient Grains Vs Modern Grainsmentioning
confidence: 99%
“…The vitamin content, such as for vitamin C, E and folic acid, are greater than those of most other grains, and there is great potential to use quinoa as a functional food ingredient in mainstay food-processing applications. Quinoa has several health benefits in high-risk groups such as children and the elderly, as well as having prebiotic and probiotic effects [41]. However, it also contains phytate, saponin, tannins and protease inhibitor as the main antinutrients [18].…”
Section: Quinoamentioning
confidence: 99%
“…To determine the level of reduction of tannins to the level preferred by consumers, an organoleptic test was conducted. Organoleptic tests in the development of low-tannin instant sorghum porridge have been studied and the results show that the addition of tapioca can increase consumer preference [10]. Breadfruit flour is processed into basic porridge (without the addition of other ingredients) so that the bitter taste caused by the compounds contained in breadfruit flour can be felt by the panelists.…”
Section: Organoleptic Testmentioning
confidence: 99%